A Feasibility Study About Using SiO2 Nanofluid Screen Mesh Wick Heat Pipe for Cooling of High-Power LEDs. Issue 9 (12th June 2016) - Wang, Yiwei; Zhang, Jianxin; Cen, Jiwen; Jiang, Fangming
Abstract : Effective and timely heat removal from high-power light-emitting diodes (LEDs) is crucial to their performance and lifetime. The strategy of using a screen mesh wick heat pipe with SiO2 nanofluid as the working fluid for LED heat dissipation is comprehensively evaluated. An experimental system is set up to study the heat transfer performance of the heat pipe. The obtained experimental results give optimal conditions/parameters for the heat pipe: 60% charging ratio, 30° incline angle, and 1wt% concentration of the nanofluid. Compared with a heat pipe using the secondary distilled water as the working fluid, the thermal resistance of the heat pipe using the SiO2 nanofluid as the working fluid is generally reduced by around 35–40% for the investigated heat load range of 1–60 W. Based on an equivalent heat conductivity of the SiO2 nanofluid heat pipe derived from the experimental results, an Icepak modeling effort for the cooling system of a 60-W LED lamp is then expended. The numerical results show that the temperature of the LED lamp remains low and quite uniform across the LED chip region, indicating the technical feasibility of using this class of heat pipes for cooling of high-power LEDs.